Harnessing the power of sphingolipids: Prospects for acute myeloid leukemia. (September 2022) - Ung, Johnson; Tan, Su-Fern; Fox, Todd E.; Shaw, Jeremy J.P.; Vass, Luke R.; Costa-Pinheiro, Pedro; Garrett-Bakelman, Francine E.; Keng, Michael K.; Sharma, Arati; Claxton, David F.; Levine, Ross L.; Tallman, Martin S.; et al.
Abstract: Acute myeloid leukemia (AML) is an aggressive, heterogenous malignancy characterized by clonal expansion of bone marrow-derived myeloid progenitor cells. While our current understanding of the molecular and genomic landscape of AML has evolved dramatically and opened avenues for molecularly targeted therapeutics to improve upon standard intensive induction chemotherapy, curative treatments are elusive, particularly in older patients. Responses to current AML treatments are transient and incomplete, necessitating the development of novel treatment strategies to improve outcomes. To this end, harnessing the power of bioactive sphingolipids to treat cancer shows great promise. Sphingolipids are involved in many hallmarks of cancer of paramount importance in AML. Leukemic blast survival is influenced by cellular levels of ceramide, a bona fide pro-death molecule, and its conversion to signaling molecules such as sphingosine-1-phosphate and glycosphingolipids. Preclinical studies demonstrate the efficacy of therapeutics that target dysregulated sphingolipid metabolism as well as their combinatorial synergy with clinically-relevant therapeutics. Thus, increased understanding of sphingolipid dysregulation may be exploited to improve AML patient care and outcomes. This review summarizes the current knowledge of dysregulated sphingolipid metabolism in AML, evaluates how pro-survival sphingolipids promote AML pathogenesis, and discusses the therapeutic potential of targeting these dysregulated sphingolipid pathways.